Valores, Atitudes e Simbolismos: Estudo da Percepção dos Frequentadores do Parque Mariano Procópio, Juiz de Fora, MG - Costa, Renata Geniany da Silva (2011)
The number of studies that seek to understand the relationship between environment and humans are increasingly growing. The environmental perception presents a consistent basis for understanding the inter-relationship between man and environment. For this reason the environmental perception permeates all the entire theoretical basis which this study aimed to: understand the relationship established between people in their daily lives and Mariano Procopio Park in Juiz de Fora-MG, from a study of perceptions of goers. We understand that motives and satisfactions are closely linked to the relationship established between the subject and these spaces. Thus, these spaces need to be planned considering the subjective aspects of choice and use looking at the experience of individuals who attend it. To investigate these subjective aspects of the subject's experience with the Mariano Procopio Park we used the theoretical framework guided by the Cultural-Humanistic geography and the work of geographer Yi-Fu Tuan. This cha n of thought has guided the qualitative research on understanding and analysis of the goals of this work. For investigation we chose the desired interrogation methodology suggested by Anne Whyte, whose technique used was the interview. The interviews were administered to subjects within the Mariano Procopio park s goers and provided information relevant about the planning of public spaces such as parks. The results were structured from the analysis of discourse, whereas the uses, motivations, symbols, attitudes and perceptions, are guided by values associated with a space-sociohistorical discourse. In our analysis, we see a close relationship with the aders of the park, which mainly because of its infrastructure and its garden, brings pleasure to visitors and offers a distinctive place for leisure and recreation.